The Perceived Role of Leadership and Community Support in the Performance of Community-Based Rural Homestay (CBRH) Programme in Malaysia - Kayat, Kalsom; Zainuddin, Nur Farrah Ain; Ramli, Razamin; Kasim, Maznah Mat (International Review of Management and Marketing, 2016)
In Malaysia, CBRH is promoted as a tourism product and expected to perform as a means to develop rural communities through their engagement in small tourism businesses. Both financial and non-financial supports have been provided to the homestay operators by different government agencies to enable them to serve visitors and eventually to sustain their performance. This paper presents a descriptive study on CBRH operators’ perceptions toward two variables that may influence CBRH’s performance. Specifically, it explores the influential roles that can be played by leadership and community support which have been mentioned by the literature as probable influencer to the performance of a CBT similar to the CBRH programme. The results show that homestay operators perceived leadership as a more predominant factor than community support in ensuring the performance of their homestay. Keywords: Leadership, Community Support, Community-Based Rural Homestay Programme JEL Classifications: O2, Q3, R1